Critical Reflection on the Rights of Creditors in Case of Insufficiency of Assets in OHADA Collective Procedures Law - Kontchop, Hilarion; Tsala, Edith Nadège Fopa (International Journal of Law and Society, 2023)
The procedure of liquidation of assets can be closed for the extinction of liabilities or for insufficient assets. The court may then, at the request of any interested person or ex officio, at any time during the proceedings and after a report by the official receiver, close the proceedings. In case of insufficiency of assets, the business disappears and, perhaps, the hope of any payment to creditors as well. For a long time, it was accepted that the closure for lack of assets allows creditors to resume individual proceedings against the debtor, especially if the latter returns to better circumstances. This traditional solution has been abandoned. According to OHADA Uniform Act on the organisation of collective procedures for the settlement of liabilities, revised on 10 December 2015, closure for insufficiency of assets no longer automatically gives creditors the right to take individual action. Thus, when a liquidation leads to a shortage of assets, the satisfaction of creditors remains uncertain. The objective of this study is to show that despite this reform, the protection of creditors’ rights has not changed significantly in the event of insufficient assets. Indeed, any possible recourse to the recovery of their claims remains paralysed by certain measures that infringe their rights. The infringements can be described as severe or moderate depending on the case.
Keywords: Closure (psychology); Collective Proceedings; Creditors; Debtor; Insufficiency of Assets; Liquidation; Settlement (finance)